Standardized patients in psychiatry – the best way to learn clinical skills? - Himmelbauer, Monika (BMC Med Educ, 2018)
BACKGROUND: Standardized patients (SP) have been successfully utilized in medical education to train students’ communication skills. At the Medical University of Vienna communication training with SPs in psychiatry is a mandatory part of the curriculum. In the training, the SP plays the role of four different patients suffering from depression/suicidal tendencies, somatoform disorder, anxiety disorder, or borderline disorder while the student attempts to gather the patient’s medical history. Both the instructor and SP then give the student constructive feedback afterwards. METHOD: The aim of the study was to evaluate the quality of the SP’s roleplay and feedback, using a self-created questionnaire. Additionally, we wanted to gauge the differences between the students’ and teachers’ evaluations of the SP’s role playing performance and feedback. RESULTS: The questionnaire was completed by 529 students and 29 teachers who attended the training. Overall, both students and teachers evaluated the SPs’ performance and feedback very well. In comparison to the responses given by the teachers, more students reported that the “SP overacted” while fewer students believed that the “SP could be a real patient”. The feedback given by the SP was evaluated similarly by students and teachers, suggesting that students are able to recognize the quality of constructive feedback. Furthermore, the SP’s quality of roleplaying was evaluated as the poorest while playing the psychiatric disorder “depression/suicidal tendencies.” CONCLUSIONS: Our study showed that students and teachers appreciate SPs’ competence of role play and of giving feedback. However, further studies should be performed to figure out why both students and teachers alike evaluated the played psychiatric disorder “depression/suicidal tendencies” to be the worst.